Balanced Scorecard Sebagai Alat Manajemen Strategi Untuk Mengukur Kinerja Sekolah Islam Terpadu (SIT) Bina Insani Cahaya Abadi - Salim, Salim; Hanifa, Imam Abu; Ismawati, Iis (Owner : Riset dan Jurnal Akuntansi, 2025)
Competition in the business world brings major changes in all operational activities, marketing and human resource management. This requires organizations to better prepare themselves so they can be accepted and compete on the global stage. This condition makes management work hard to prepare, perfect and look for new strategies so that the organization is able to survive and develop in national and international competition. SIT (Integrated Islamic School) Bina Insani Cahaya Abadi is a non-profit Integrated Islamic School in Serang Regency. With TKIT, SDIT, SMPIT and SMAIT education programs Schools must survive in the midst of globalization which has a big impact on the world of education in Indonesia, including schools being used as business media so that education in Indonesia is controlled by capital owners. In the end, school administrators will be at a crossroads between maintaining their idealism as educational people or following the flow of globalization which leads to the commercialization of education. Balanced Scorecard is a comprehensive performance measurement method. The focus of the Balanced Scorecard measurement includes the following: (1) Clarifying and translating the company's vision and strategy, (2) Communicating and conveying strategic goals with performance measures, (3) Planning, setting targets and aligning strategic programs, (4) Developing feedback and learning strategies to improve continuously in the future. In this research approach, the author uses a qualitative descriptive narrative approach. Some sources of qualitative data are interview notes, transcripts of focus groups answering open questions, transcriptions of video recordings, reports of experiences with a product.